(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This paper examines modern approaches to teaching native and foreign languages within the framework of intercultural communication. It explores innovative pedagogical technologies, the communicative method, multimodal learning, and mechanisms for developing intercultural competence. The study also discusses the impact of digital tools, strategies for increasing learner engagement, and the relationship between language and culture. The findings provide theoretical and practical recommendations for improving the effectiveness of contemporary language education.